Anti-cyclic citrullinated peptide antibodies, 28-joint Disease Activity Score, and magnetic resonance imaging bone oedema at baseline predict 11 years' functional and radiographic outcome in early rheumatoid arthritis. (2nd January 2019) - Hetland, ML; Østergaard, M; Stengaard-Pedersen, K; Junker, P; Ejbjerg, B; Jacobsen, S; Ellingsen, T; Lindegaard, H; Pødenphant, J; Vestergaard, A; Jurik, AG; Krogh, NS; et al.
Abstract : Objective : To investigate the clinical and radiographic status, and to identify baseline predictors of functional status and erosive progression at 11 years' follow-up of early rheumatoid arthritis (RA) patients. Methods : Patients enrolled in the Danish investigator-initiated randomized controlled CIMESTRA trial, which investigated a 2 year treat-to-target intervention with methotrexate and intra-articular glucocorticoids with or without cyclosporine, were followed up. The 28-joint Disease Activity Score (DAS28), Health Assessment Questionnaire (HAQ) score, and total Sharp van der Heijde score (TSS) were assessed at baseline and 11 years. Baseline magnetic resonance imaging (MRI) of unilateral wrists was scored (OMERACT RAMRIS). Multivariable linear regression analyses of baseline variables [TSS, HAQ, DAS28, age, anti-cyclic citrullinated peptide (anti-CCP) status, gender, MRI erosion score, MRI synovitis score, MRI bone marrow oedema score] were performed in 96 patients with HAQ11yrs and ∆TSS0–11yrs as dependent variables. Since outcomes were similar in the two treatment arms, data were pooled. Results : In total, 120 of 160 patients completed 11 years' follow-up. They were 63 (55–72) years old, 68% were in DAS28 remission (≤ 2.4), HAQ11yrs was 0.25 (0–0.75), mean ∆TSS0–11yrs was 0.96 ± 1.52 units/year; 53%, 20%, and 27% received conventional treatment, biologics, and no treatment, respectively; and 34% had not progressed radiographically since baseline. Increased DAS28 (p = 0.02) and anti-CCP (p = 0.03) predicted HAQ11yrs, whereas anti-CCP (p = 0.03) and MRI bone marrow oedema (p = 0.01) predicted ∆TSS0–11yrs in multivariable analyses. Conclusions : Early and strict synovitis suppression with methotrexate and intra-articular glucocorticoids led to persistently high remission rates and limited erosive progression at 11 years. In this well-treated cohort, baseline anti-CCP status, DAS28, and MRI bone marrow oedema predicted functional status and/or erosive progression.